2015
DOI: 10.1039/c5ob01450f
|View full text |Cite
|
Sign up to set email alerts
|

Selective binding and extraction of aqueous dihydrogen phosphate solutions via three-armed thiourea receptors

Abstract: A series of neutral anion receptors with one to three thiourea arms were synthesized and their binding to tetrabutylammonium chloride, acetate, and dihydrogen phosphate salts in aqueous DMSO mixtures was examined. The three-armed thiourea host was found to strongly and selectively bind H2PO4(-) even in DMSO solutions containing up to 30% water. This enabled the dihydrogen phosphate salt to be extracted from water into chloroform in its dibasic form despite the high heat of the hydration of HPO4(2-).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…Thioureas 1−3 were prepared as previously described. 17 Compound 1 was dissolved in methanol whereas a dimethyl sulfoxide/methanol mixture was used for 2 and 3. These solutions were individually added to separate aqueous methanol mixtures containing NaX, where X = Cl, OAc, and H 2 PO 4 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thioureas 1−3 were prepared as previously described. 17 Compound 1 was dissolved in methanol whereas a dimethyl sulfoxide/methanol mixture was used for 2 and 3. These solutions were individually added to separate aqueous methanol mixtures containing NaX, where X = Cl, OAc, and H 2 PO 4 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…This is different than what is observed in aqueous DMSO solutions where only the binding of H 2 PO 4 − by 3 operates in a cooperative manner and makes use of all three thiourea arms. 17 A single thiourea moiety is used in the other cases, and this indicates that the solvent and/or counterion play a key role and must be responsible for this difference. Dynamics calculations exploring this effect are warranted and would be useful.…”
mentioning
confidence: 99%
“…The bis‐thiourea derivative 80 was prepared quantitatively from reaction of the diamine 79 , obtained from palladium‐catalyzed coupling of 2‐pivaloylaminophenylboronic acid 78 and 1,3‐dibromobenzene 77 , with aryl isothiocyanate 4 in THF under nitrogen (Scheme ) .…”
Section: Synthetic Routes To Bis‐thioureasmentioning
confidence: 99%
“…Multi-oxo anions are of particular relevance in this regard. [9][10][11][12][13][14][15][16][17][18][19][20] For example, a triptycene-derived C 3v -symmetric receptor with anion-binding pyrrole and amide groups was reported by Jurczak et al for the selective recognition of H 2 PO 4 anions. Phosphate anions are acknowledged to affect biological and ecological systems considerably, and a great deal of attention is set on further understanding their impact.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Thus, phosphate-binding receptors have become an important target in anion-coordination chemistry, and there have been several recent reports of synthetic receptors designed to bind phosphate anions selectively. [9][10][11][12][13][14][15][16][17][18][19][20] For example, a triptycene-derived C 3v -symmetric receptor with anion-binding pyrrole and amide groups was reported by Jurczak et al for the selective recognition of H 2 PO 4 anions. [10] Johnson et al have shown selective recognition of H 2 PO 4 anions over more basic AcOand other anions by an arylethynyl-based bis(urea) receptor.…”
Section: Introductionmentioning
confidence: 99%